Computer Security Fundamentals - Easttom, Chuck (Pearson IT Cybersecurity Curriculum, 2023)
The perfect beginner's guide for anyone interested in a computer security career. Dr. Chuck Easttom brings together complete coverage of all basic concepts, terminology, and issues, along with all the skills you need to get started. Drawing on 30 years of experience as a security instructor, consultant, and researcher, Easttom helps you take a proactive, realistic approach to assessing threats and implementing countermeasures. Writing clearly and simply, he addresses crucial issues that many introductory security books ignore, while addressing the realities of a world where billions of new devices are Internet-connected. This guide covers web attacks, hacking, spyware, network defense, security appliances, VPNs, password use, and much more. Its many tips and examples reflect new industry trends and the state-of-the-art in both attacks and defense. Exercises, projects, and review questions in every chapter help you deepen your understanding and apply all you've learned.